Recurrence of herpes simplex virus endotheliitis in a Descemet membrane endothelial keratoplasty graft: mimicking fungal interface infection. Issue 5 (6th May 2019) - Basak, Samar K; Basak, Soham
Abstract : Recurrence of herpes simplex virus (HSV) keratitis is a problem of keratoplasty and the prognosis is often poor in spite of oral acyclovir (ACV) prophylaxis. This 64-year-old woman was a known case of recurrent HSV endotheliitis with irreversible corneal oedema in the left eye for 2 years. She underwent Descemet membrane endothelial keratoplasty with intraocular lens implantation under perioperative oral ACV and prednisolone. After 4 weeks, her cornea cleared with the best-corrected vision of 6/9. After 2.5 months, she presented with sudden photophobia and visual loss. An increasing focal endothelial lesion was noticed even after oral ACV. Suspecting fungal interface infection, anterior chamber tap was done for PCR for panfungal and viruses. It was only positive for HSV. Oral ACV was changed to oral valacyclovir. The patient responded dramatically within 2 weeks, and after 12 weeks, the lesion disappeared completely, leaving behind a faint scar with 6/9 p vision. Oral valacyclovir, a prodrug of ACV, may work better than oral ACV.